Effect of plain strain deformation on grain strengthening mechanism of Fe-Al2O3 metal matrix nanocomposites. (January 2021) - Gupta, Vinod Kumar; Harshit, Kumar; Jha, Arun Kant; Kumar, Devendra; Sadasivuni, Kishor Kumar; Gupta, Pallav
The present paper reports the effect of plain strain deformation on grain strengthening mechanism of iron (Fe) - alumina (Al2 O3 ) Metal Matrix Nanocomposites (MMNCs) fabricated through powder metallurgical (P/M) processing. Specimens for the present study were weighed in required amount, ball milled, compacted at a load of 5, 6 and 7 tons followed by sintering in an atmospheric controlled furnace at 1100 °C for 1 hour. Plain strain deformation of samples was carried out at a load of 5 tons under different interfacial condition i.e. dry, solid lubricant and liquid lubricant. XRD studies reveal the formation of iron, alumina and nano iron-aluminate (FeAl2 O4 ) phases respectively. Maximum average sintered density investigated for the specimen is found to be 4.6179 gm/cc compacted under 7 tons of load and minimum sintered density is found to be 4.4572 gm/cc for specimen compacted under 5 tons of load. Overall, fabricated Fe-Al2 O3 metal matrix nanocomposites with powder metallurgy route when characterized for plain strain deformation shows strengthening between grain and grain boundary which can be a good candidate material for application in railways especially while designing railway structures and tracks.